Perceived Effects of Technology-Based Goal Setting on Lifestyle Behavior Change in Athletes - Abalorio , Bridget; Muñoz, Nayelli (Health Nexus, 2025)
This study aimed to explore athletes’ perceptions of how technology-based goal-setting tools influence their lifestyle behavior change. A qualitative exploratory design was employed using semi-structured interviews with 27 athletes from various sports disciplines in Peru. Participants were selected through purposeful sampling based on their experience with technology-assisted goal-setting tools such as fitness apps, wearables, and performance dashboards. Data collection continued until theoretical saturation was reached. All interviews were transcribed, translated into English, and analyzed thematically using NVivo 12 software, following Braun and Clarke’s six-phase framework. Rigor was ensured through independent coding, member checking, and peer debriefing. Analysis revealed four main themes: (1) Motivational Enhancement (e.g., increased accountability, gamification appeal, goal commitment), (2) Behavioral Regulation (e.g., habit formation, sleep pattern control, diet monitoring), (3) Psychological and Emotional Impact (e.g., reduced stress, confidence improvement, emotional engagement), and (4) Contextual and Environmental Influences (e.g., technological accessibility, coach endorsement, institutional support). Athletes reported that digital tools not only improved their commitment and consistency but also positively affected emotional regulation and lifestyle structure. However, some participants noted barriers such as limited digital literacy and overdependence on metrics. Technology-based goal-setting tools are perceived by athletes as effective instruments for promoting healthy lifestyle behaviors by enhancing motivation, structure, and emotional resilience. However, their effectiveness depends on individual readiness, environmental support, and mindful integration into training culture. These tools can be leveraged in athlete development programs but require culturally sensitive, user-centered implementation to avoid unintended psychological pressures.